Clinical Translational Studies of Kisspeptin and Neurokinin B - Hunjan, Tia; Abbara, Ali (Seminars in Reproductive Medicine, 2019)
Kisspeptin and neurokinin B (NKB) are hypothalamic neuropeptides that are vital for reproductive health. An absence of either kisspeptin or NKB signaling results in hypogonadotrophic hypogonadism and a failure to proceed through puberty. In recent years, several studies have demonstrated potential avenues for the clinical utility of medications that act through these pathways in the assessment and treatment of reproductive disorders. Kisspeptin acts to stimulate hypothalamic gonadotrophic-releasing hormone (GnRH) secretion from the hypothalamus. Kisspeptin induces gonadotrophin secretion in both healthy men and women, and in women with reproductive disorders such as hypothalamic amenorrhea (HA). Kisspeptin-based treatments hold promise for use during in vitro fertilization (IVF) treatment; a bolus of kisspeptin-54 induces an LH surge of 12 to 14 hours of duration sufficient to induce oocyte maturation, but with markedly reduced rates of the most significant complication of IVF treatment, ovarian hyperstimulation syndrome (OHSS). Kisspeptin could also be used chronically to restore reproductive health in patients with functional hypogonadism, such as those with HA. Furthermore, kisspeptin has potential as a diagnostic test of hypothalamic function; a “kisspeptin test” could be used in children with delayed puberty to identify the subset with genetically determined deficits in hypothalamic pathways (congenital hypogonadotrophic hypogonadism [CHH]). In addition to its role in hypothalamic GnRH pulse generation, NKB plays a critical role in the occurrence of one of the most troubling symptoms of the menopause, the “hot flush.” Neurokinin-3 receptor (NK3R) antagonists are highly effective as treatments for hot flushes in postmenopausal women, with several compounds now in late-phase development. Furthermore, NK3R antagonism leads to a reduction in LH secretion by reducing GnRH pulsatility in the hypothalamus and has been shown to reduce androgen levels in women with polycystic ovary syndrome (PCOS) (in whom GnRH pulsatility is often increased). In summary, although further detailed evaluation in several clinical settings is ongoing, medications based on kisspeptin and NKB pathways have prodigious potential in the assessment and treatment of reproductive disorders.
Keywords: Kisspeptin; neurokinin B; reproductive disorders